BN-MWCNT/PPS core-shell structured composite for high thermal conductivity with electrical insulating via particle coating. (28th September 2016) - Kim, Kiho; Kim, Jooheon
Abstract: Polyphenylene sulfide (PPS) is a promising material as an important engineering thermoplastic polymer for various industrial applications. Here we report a highly thermally conductive PPS composite containing boron nitride (BN) and multiwalled carbon nanotubes (MWCNTs) as a thermally conductive filler. The composite was prepared by the particle coating method into polymer pellets in order to obtain high thermal conductivity with low filler concentration, and thus overcome the drawbacks of melt mixing. A comparison between conventional melt mixing and the proposed method showed that the continuous connection of particles at the surface of each pellet led to great enhancement of thermal conductivity. Moreover, the electrically insulating BN layer effectively interrupted electron conduction, which is the major problem with using MWCNTs as a thermally conductive filler, despite their superior thermal conductivity. Our results show that the particle coating method may be used as a promising composite fabrication method for engineering plastics-based thermally conductive materials. Graphical abstract: Highlights: Core-shell structured conductive composite was fabricated via particle coating. Particle-shell generated well connected heat flow path. High Thermal conductivity was obtained at the small filler concentration. Electrical conductivity of MWCNT composite was reduced by BN coating.